Znaczenie wyglądu zewnętrznego dziewic i mnichów w formacji duchowej w klasztorach Galii i Hiszpanii (VI-VII w.) - Wygralak, Paweł (Vox Patrum, 2018)
The article discusses the influence of the way of the monastic dress code on helping nuns and monks stay on their spiritual path during formation. The Focus of the study are the rules for nuns and monks developed in the 6th and 7th centuries in Gaul and Spain. The authors of the rules were convinced that the very strict requirements regarding the clothing, as well as the behavior, of consecrated persons, serve the practice of seeking virtue through poverty, obedience and humility. It was required that all the inhabitants of a monastery should wear simple habits with natural colors that no one could consider to be their property. Attention was also paid to the asceticism of sight and the way of walking, which served to preserve the virtue of purity. For the same reason, one was not allowed to take too many baths, except in the case of disease. The whole life of the celibate nuns and monks should be focused on the caring for the development of their spiritual life, and not on the pursuit of external appearance. The humble acceptance of poor attire, temperance in care for the body, and the ability to exercise self-control his eyesight, testified to the spiritual maturity of the nun and the monk.